POPULATION DYNAMICS OF INDIAN MACKEREL BASED ON DATA PROM MANGALORE DURING 1967-1975 - Yohannan, T M (Indian Journal of Fisheries, 2011)
The total mortality rate (Z), as on data collected at Mangaloreduring 1967-75, ranged between 2.54 and 6.21. Since the total mortality had noregression on Ashing intensity the natural mortality rate (M) was calculated as1.5 from the effective life span of mackerel. K,t„ and WQ, values were estimatedbased on the growth in weight. The studies indicated that mackerel can withstandheavy fishing mortalities (F) and the value of F that gives the maximum yield is6.00. The recommended age at entry into the exploited phase ( t . ) is 8 monthsinstead of the present 6 months. Increasing the F value to 6.00 and tp. to 8 monthsit is found that the existing quantity of the average standing stock can give anaverage annual catch of 1,98,870 tonnes instead of the present 96,451 tonnes.